2015
DOI: 10.1002/masy.201400104
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Dichlorocarbene Modified Butadiene Rubber and Its Thermal Properties

Abstract: Summary: Dichlorocarbene modified butadiene rubber (DCBR) was prepared from butadiene rubber (BR) via an alkali hydrolysis of chloroform with using cetyltrimetylammonium bromide (CTAB) as a phase transfer agent. The chemical structure of DCBR was characterized by a fourier transform infrared spectroscopy and 1 H-and 13 C-nuclear magnetic resonance spectroscopy. The chlorine content in DCBR matrix was extracted by acid digestion method and estimated based on a volhard method. The chlorine content of DCBR increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The vulcanizates of BR have superior tensile strength, low hysteresis loss, good wear resistance, low rolling resistance, and for these reasons about 70% of the total production of BR is used in the tire industry. Butadiene rubber is commonly blended with other rubbers instead of being used alone [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The vulcanizates of BR have superior tensile strength, low hysteresis loss, good wear resistance, low rolling resistance, and for these reasons about 70% of the total production of BR is used in the tire industry. Butadiene rubber is commonly blended with other rubbers instead of being used alone [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The DCBR was prepared by dichlorocarbene modification via the alkaline hydrolysis of CHCl 3 as described in the previous report . 10 g of BR dissolved in 150 mL toluene in a 2‐necked round‐bottomed flask was added by 0.002 mol of the phase transfer agent (CTAB or TEAC).…”
Section: Methodsmentioning
confidence: 99%
“…The DCBR was prepared by dichlorocarbene modification via the alkaline hydrolysis of CHCl 3 as described in the previous report. 33 10 g of BR dissolved in 150 mL toluene in a 2-necked round-bottomed flask was added by 0.002 mol of the phase transfer agent (CTAB or TEAC). The solution was stirred at room temperature (RT; approximately 25°C), 40°C or 50°C for 5 minutes, then CHCl 3 (30 mL) and 50% (w/w) NaOH (35 mL) were added.…”
Section: Preparation Of Dcbrmentioning
confidence: 99%
“…The most convenient and efficient method reported for the generation of dihalocarbene is the hydrolysis of chloroform (CHCl 3 ) with aqueous alkali metal hydroxide in the presence of a phase transfer agent. [14][15][16] We have reported that the dichlorocarbene-modified styrene butadiene rubber (SBR) shows better flame retardancy and excellent oil resistance compared to other chlorinecontaining rubbers. 17 The oil and solvent diffusion process depends on free volume within the elastomer matrix, polarity of polymer, cross-link density, temperature, and the size of the penetrant molecules.…”
Section: Introductionmentioning
confidence: 99%